Tatear o mundo: poéticas e diálogos entre Ana Martins Marques e Adriana Lisboa - Paiva, Natascha Gomes (2024)
The purpose of this research is to investigate how the poetic works O livro dos jardins, by Ana Martins Marques (2019), and O vivo, by Adriana Lisboa (2021), reveal the power of poetic language in dialogue with the Anthropocene crisis in contemporary times. To achieve this general objective, the aesthetic procedures used by the poets in the corpus of analysis are examined, especially those related to the expression of lyrical subjectivity and its relationship with otherness. From this perspective, this study problematizes the dehumanization of man in the face of the humanity of others, considering the split between man and the environment. To this end, some hypotheses were outlined: the poetic writings of Ana Martins Marques e Adriana Lisboa build the relationship between humans and the environment, through poetics that highlight a new humanist and ecological thought, also highlighting animal and plant subjectivities; the author’s poetic writings suggest a dialogue with the philosophy of nature, proposing the construction of their poetics based on the interrelationship between human experience and nature, plant and animal subjectivities, in dialogue and communion with nature, highlight the poetic time constructed in the works. Such hypotheses were tested considering the theoretical support of several authors from fields of Literature and Philosophy, such as Ailton Krenak, Byung-Chul Han, Evando Nascimento, Maria Esther Maciel and Michel Collot. The argument is developed over four chapters: in the first, some reflections are presented on the Anthropocene crisis in the contemporary world and the search for a new humanism and an ecocritical lineage as possibilities for deconstructing the dullness of human senses and actions; in the second, the work O livro dos jardins is analyzed and the link between its poems and poetic experience and vegetal alterity; in the third, poems from the book O vivo are analyzed and their connection with subjectivity animal and vegetal otherness; and, finally, in the fourth chapter, the confrontation between the two works is studied, having as its foundation the confrontations of the Anthropocene and the fracture between man and the environment. Finally, the contribution of contemporary Brazilian poetry I the voice of Ana Martins Marques and Adriana Lisboa reveals in the interlocution with current emergencies, thus highlighting the sensitive work with language carried out by the authors